Snake hair : the story of Medusa - Spinner, Stephanie (New York : Grosset & Dunlap, 1999)
Recounts how the Greek hero Perseus vanquished the serpent-haired Medusa whose gaze turned people to stone.
Keywords: Medusa (Greek mythology)-Juvenile literature; Perseus (Greek mythology)-Juvenile literature; Medusa (Greek mythology); Perseus (Greek mythology); Mythology, Greek